2022
DOI: 10.1371/journal.pone.0265769
|View full text |Cite
|
Sign up to set email alerts
|

Decreased accuracy of erythrocyte sedimentation rate in diagnosing osteomyelitis in diabetic foot infection patients with severe renal impairment: A retrospective cross-sectional study

Abstract: Background Rapid diagnosis and treatment of diabetic foot osteomyelitis (DFO) could reduce the risk of amputation and death in patients with diabetic foot infection (DFI). Erythrocyte sedimentation rate (ESR) is considered the most useful serum inflammatory marker for the diagnosis of DFO. However, whether severe renal impairment (SRI) affects its diagnostic accuracy has not been reported previously. Objective To investigate the accuracy of ESR in diagnosing DFO in DFI patients with and without SRI. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Acupuncture Treatment. Tang Xiaohui et al through meta-analysis concluded that moxibustion has a significant clinical effect in the treatment of diabetic foot [45]. According to the method of random number table, 80 patients with DF were divided into the experimental group and the control group [46].…”
Section: Local Wound Treatment Professor Wang Shuang Et Al Treated Df...mentioning
confidence: 99%
“…Acupuncture Treatment. Tang Xiaohui et al through meta-analysis concluded that moxibustion has a significant clinical effect in the treatment of diabetic foot [45]. According to the method of random number table, 80 patients with DF were divided into the experimental group and the control group [46].…”
Section: Local Wound Treatment Professor Wang Shuang Et Al Treated Df...mentioning
confidence: 99%
“…14,25 The most commonly used parameters are erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and white cell count (WCC), although their circulating levels may be altered in several conditions with differences in sensitivity and specificity. 11,14 Of note, among bone turnover markers, there were no differences in vitamin D serum levels between the study groups. This result may be related to the high rate of vitamin D deficiency/insufficiency in patients with diabetes.…”
Section: Discussionmentioning
confidence: 90%
“…Among biochemical markers, acute phase reactants, which are produced by the liver during inflammatory states, may be measured to distinguish non‐infected ulcers, DFI, and OM 14,25 . The most commonly used parameters are erythrocyte sedimentation rate (ESR), C‐reactive protein (CRP), and white cell count (WCC), although their circulating levels may be altered in several conditions with differences in sensitivity and specificity 11,14 . Of note, among bone turnover markers, there were no differences in vitamin D serum levels between the study groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations